Awareness about anti-tobacco public education campaigns: a comparative study of anti-smoking and smokeless tobacco campaigns among urban and rural high school children - Bahl, Ina; M., Bhanu; B. A., Aravind; Haridas, Radhika; H. K., Dinesh (International Journal Of Community Medicine And Public Health, 2024)
Background: Even as propagation of anti-tobacco campaigns is widespread, data on its awareness and efficacy remains obscure. Where rising levels of tobacco consumption among the youth not only poses a risk to individual health but also jeopardises the country’s socioeconomic prospects, the need of the hour is to recognize youth centric information, education, communication (IEC) campaigns. Methods: A descriptive cross-sectional study was carried out among high school students from a selected urban (n=172) and rural (n=172) school. A semi-structured pretested questionnaire was employed to collect information. Data obtained was summarized using descriptive statistics and Chi square test. Results: The awareness about anti-tobacco (smokeless) campaign was found to be 98.4 % among urban and 77.6% among rural high school children, whereas, the awareness about anti-smoking campaign was found to be 98.3% among urban and 76.2% among rural high school children. Overall awareness among urban children was significantly higher than that among rural children (p<0.001). Conclusions: The study assessed the extent to which anti-smoking and anti-tobacco (smokeless) campaigns have successfully reached the target masses and to what extent they have been successful in communicating the hazards effectively which is crucial to exterminate the tobacco related problems.